Extracorporeal Life Support for Pediatric Heart Failure - Burke, Christopher R.; McMullan, D. Michael (Frontiers in Pediatrics, 2016)
Extracorporeal life support (ECLS) represents an essential component in the treatment of the pediatric patient with refractory heart failure. Defined as the use of an extracorporeal system to provide cardiopulmonary support, ECLS provides hemodynamic support to facilitate end organ recovery and can be used as a salvage therapy during acute cardiorespiratory failure. Support strategies employed in pediatric cardiac patients include bridge to recovery, bridge to therapy, and bridge to transplant. Advances in extracorporeal technology and refinements in patient selection have allowed wider application of this therapy in pediatric heart failure patients.